(untitled) (Research, Society and Development, 2021)
The objective of this study was to evaluate the quality of white-fleshed dragon fruit (Hylocereus undatus) at harvest and postharvest to determine fruit quality and the feasibility of harvesting the fruits at different outer fruit color stages. The treatments consisted of four peel color stages – S1 (<25% red peel), S2 (25%-49% red peel), S3 (50% to 75% red peel) and S4 (>75% red peel) – and two evaluation times (at harvest and one day after full red peel color), which corresponded to 1, 3, 5 and 7 days after harvest for the S4, S3, S2 and S1 color stages, respectively. The total, peel and pulp weights, pulp yield, peel thickness, pulp firmness, pH, total soluble solids and peel, scale and pulp colors were evaluated. The peel and scale colors are reliable indicators of fruit quality. It is possible to extend the postharvest shelf life of the fruits by harvesting at the S1 stage, but this negatively affects yield and final quality; the fruits are smaller and less sweet, making harvesting unfeasible at this timepoint. Despite the higher yield and quality of fruits harvested at a more advanced ripeness stage (S4), the postharvest shelf life is considerably reduced. Thus, fruits at stages S2 or S3 should be harvested to obtain higher yield and quality.